Early warning systems for biodiversity in southern Africa – How much can citizen science mitigate imperfect data?. (April 2017) - Barnard, Phoebe; Altwegg, Res; Ebrahim, Ismail; Underhill, Les G.
Abstract: It is a hard reality that virtually all countries, no matter how well resourced, take conservation and land use decisions based on highly patchy and imperfect data - if indeed any data at all. Despite a mushrooming of scientific evidence and journals in the past decade, and open-access provision of many expensive global datasets, developing countries in particular often have to make do with inaccurate and coarse-scale global data, in the absence of targeted, local data to solve immediate conservation problems. To what extent can citizen science data compensate for the patchiness of conventional government-gathered scientific data in order to support planning, policy and management? We demonstrate how southern Africa's citizen science-based "early warning system for biodiversity" is used to support land-use planning and conservation decisions, including Red List, strategic and project-based environmental impact assessments and national protected area expansion and implementation strategies. This system integrates volunteer-based species atlases such as the Protea Atlas Project and Southern African Bird Atlas Project (SABAP), species population monitoring such as the Custodians of Rare and Endangered Wildflowers (CREW) project, and site-based rapid assessment and monitoring such as MyBirdPatch and BioBlitz. Countries in southern Africa are on a sharp continuum of research capacity, funding, political engagement and own datasets. Yet there is the capacity for adaptive management systems based in significant part on civil society volunteerism. Crucially, these must be underpinned by statistically sound, simple, repeatable scientific protocols, which are still rare in Africa.